THE IMPACT OF THE SOUTH AFRICAN ELECTORAL SYSTEM ON LEGISLATIVE OVERSIGHT - Maganoe, Shadi (Obiter, 2024)
This study investigates the relationship between the South African electoral system and its consequential effects on legislative oversight. Through an analysis of historical data, electoral structures, and parliamentary dynamics, this study aims to illuminate the various ways in which the chosen electoral system shapes the nature and efficacy of legislative oversight mechanisms. The study delves into the features of South Africa’s electoral model, exploring how proportional representation and constituency-based elements influence the conduct of elected representatives in Parliament. In addition, this study assesses the implications of these electoral dynamics for the ability of parliamentary bodies to oversee effectively the conduct of the executive branch in order to ensure accountability and transparency in the governing process. By examining the impact of one-party dominance in Parliament as a consequence of the electoral system, this study provides insights into the intricate interplay between electoral systems and the crucial function of legislative oversight in fostering a robust democratic system.